Analysis of Numerical Method for Diffusion Equation with Time-Fractional Caputo–Fabrizio Derivative - Hanxiao Wang; Xindong Zhang; Ziyang Luo; Juan Liu (Journal of Mathematics)
In this paper, we propose a high-precision discrete scheme for the time-fractional diffusion equation (TFDE) with Caputo-Fabrizio type. First, a special discrete scheme of C-F derivative is used in time direction and a compact difference operator is used in space direction. Second, we discuss the convergence of the proposed method in discrete L1-norm and L2-norm. The convergence order of our discrete scheme is Oτ2+h4, where τ and h are the temporal and spatial step sizes, respectively. The aim of this paper is to show that fractional operator without singular term is very useful for improving the accuracy of discrete scheme.